2022
DOI: 10.1139/cgj-2020-0624
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of moisture content in sandy beach environments from multispectral satellite imagery

Abstract: A framework for estimating moisture content from satellite-based multispectral imagery of sandy beaches was tested under various site conditions and sensors. It utilizes the reflectance of dry soil and an empirical factor c relating reflectance and moisture content for specific sediment. Here, c was derived two ways: first, from in-situ measurements of moisture content and average NIR image reflectance; and second, from laboratory-based measurements of moisture content and spectrometer reflectance. The propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…These estimations have been reported to have higher efficiency than other methods [44]. In addition, the moisture content is a function of the area's topography or proximity to the waterline [43]. However, no study has observed the connection between sediment moisture and spectral reflectance for topography mapping.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…These estimations have been reported to have higher efficiency than other methods [44]. In addition, the moisture content is a function of the area's topography or proximity to the waterline [43]. However, no study has observed the connection between sediment moisture and spectral reflectance for topography mapping.…”
mentioning
confidence: 98%
“…The rapid growth in satellite development has led to several studies using remote sensing techniques from the mid-1970s [37] to assess soil moisture's spatial and temporal variations [38]- [41]. When compared with the measured moisture content, spectral reflectance from satellite imagery can similarly inform the degree of wetness or dryness of different points under varying conditions in an area [42], [43]. These estimations have been reported to have higher efficiency than other methods [44].…”
mentioning
confidence: 99%